Effects of a multi-micronutrient-fortified beverage, with and without sugar, on growth and cognition in South African schoolchildren: a randomised, double-blind, controlled intervention - Taljaard, Christine; Covic, Namukolo M.; Van Graan, Averalda E.; Kruger, Herculina S.; Smuts, Cornelius M.; Baumgartner, Jeannine; Wright, Hattie H.; Jerling, Johann C. (Cambridge University Press, 2013)
Little is known about the effects of combined micronutrient and sugar consumption on growth and cognition. In the present study, we investigated the effects of micronutrients and sugar, alone and in combination, in a beverage on growth and cognition in schoolchildren. In a 2 £ 2 factorial design, children (n 414, 6-11 years) were randomly allocated to consume beverages containing (1) micronutrients with sugar, (2) micronutrients with a non-nutritive sweetener, (3) no micronutrients with sugar or (4) no micronutrients with a non-nutritive sweetener for 8-5 months. Growth was assessed and cognition was tested using the Kaufman Assessment Battery for Children version II (KABC-II) subtests and the Hopkins Verbal Learning Test (HVLT). Micronutrients decreased the OR for Fe deficiency at the endpoint (OR 0-19; 95% CI 0-07, 0-53). Micronutrients increased KABC Atlantis (intervention effect: 0-76; 95% CI 0-10, 1-42) and HVLT Discrimination Index (1-00; 95% CI 0-01, 2-00) scores. Sugar increased KABC Atlantis (0-71; 95% CI 0-05, 1-37) and Rover (0-72; 95% CI 0-08, 1-35) scores and HVLT Recall 3 (0-94; 95% CI 0-15, 1-72). Significant micronutrient £ sugar interaction effects on the Atlantis, Number recall, Rover and Discrimination Index scores indicated that micronutrients and sugar in combination attenuated the beneficial effects of micronutrients or sugar alone. Micronutrients or sugar alone had a lowering effect on weight-for-age z-scores relative to controls (micronutrients 20-08; 95% CI 20-15, 20-01; sugar 20-07; 95% CI 20-14, 20-002), but in combination, this effect was attenuated. The beverages with micronutrients or added sugar alone had a beneficial effect on cognition, which was attenuated when provided in combination.
Keywords: Anthropometric status; child micronutrient status; cognitive function; sugar